Random copolymer, fine particle adsorbent, composition for forming fine particle-adsorbing film, and film
By forming the coating with random copolymers of specific structures, the problem of poor particle rupture and adsorption effects in the prior art is solved, and the effect of efficient adsorption and inhibition of particle rupture is achieved.
Patent Information
- Application Number
- CN202380052303.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-14
- Filing Date
- 2023-07-13
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art is difficult to effectively inhibit the rupture of particles such as pollen, viruses, and house dust, and at the same time, adsorbing, causing allergens to invade the body and causing allergic symptoms.
A random copolymer is used, whose structural units are composed of specific alkyl groups, alkylene groups and hydroxyalkenyl groups. A coating is formed by randomly repeated structural units, which has high adsorption properties and inhibits microparticle rupture.
It realizes effective adsorption of particles such as pollen without rupturing them, reduces the chance of allergen substances entering the body, and significantly improves the adsorption effect of particles such as pollen, viruses, and house dust.
Smart Images

Figure CN119421909A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a random copolymer, a particle adsorbent, a composition for forming a particle-adsorbing coating, and a coating. Background Art
[0002] Particles floating in the air, such as pollen, viruses, house dust, and particulate matter (PM2.5), are substances that may have adverse effects on the human body. For example, regarding pollen, the number of people suffering from hay fever in Japan has been increasing year by year. As for hay fever, there is currently no definitive fundamental treatment established. The general way to deal with hay fever is to reduce the chances and amount of contact with pollen. In addition, regarding particles such as viruses and house dust, it is also desirable to reduce the chances and amount of contact from the perspective of preventing their effects on the human body and the onset of allergies. Furthermore, smoke, sulfur oxides (SO 2) emitted from factories, cars, ships, airplanes, volcanoes, soil, etc. x ), nitrogen oxides (NO x ), volatile organic compounds (VOCs) and other gaseous air pollutants, particulate matter and other dust can also cause respiratory diseases such as asthma and allergic diseases, so it is hoped that the chance and amount of contact can be reduced. In addition, since these substances can cause allergic symptoms when they enter the body, they need to be adsorbed in order to prevent them from entering the body.
[0003] For example, Patent Document 1 discloses an allergen adsorbing composition in which powders such as kaolin are blended in an aqueous medium at pH 3 to 7. Patent Document 2 discloses a pollen adsorbent having a specific grafted side chain on the main chain of a polymer material composed of fibers or fiber aggregates, and the grafted side chain carries triiodide ions.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2002-167332.
[0007] Patent document 2: International Publication No. 2008 / 153090. Summary of the invention
[0008] Problem that the invention aims to solve
[0009] Allergen substances exist on the surface and inside of pollen particles. After invading the body, allergen substances will bind to antibodies, thereby causing allergic symptoms. In particular, it is known that such allergen substances will be released as the pollen breaks, and allergen substances are very small compared to the pollen itself, so they can easily invade the body and reach deep into the respiratory system. In addition, if the size of particles such as viruses and house dust becomes very small, it is also easier to invade the body. For example, the adsorbent shown in Patent Document 1 aims to adsorb the allergen substances themselves released by pollen particles, but from the point of view that the allergen substances have been released, it is sometimes not effective in preventing allergens from invading the body. In addition, the adsorbent of Patent Document 2 also envisions the adsorption of released allergen proteins.
[0010] However, when adsorbing pollen, etc. without breaking them, since allergen substances are not released, it is considered that the chance of contact with allergen substances can be further reduced. Therefore, the subject of the present invention is to provide a microparticle adsorbent, in particular a pollen adsorbent, which can adsorb microparticles of pollen, virus, house dust, etc. while suppressing their breakage.
[0011] Technical means of solving problems
[0012] To solve the above problems, the present invention provides the following preferred embodiments.
[0013] [1] A random copolymer comprising a structural unit represented by formula (I) and a structural unit represented by formula (II):
[0014] [Chemistry 1]
[0015]
[0016] [In formula (I) and (II):
[0017] R 1 and R 3 Each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms;
[0018] R 2 It represents an alkyl group with 1 to 6 carbon atoms;
[0019] R 4 It represents an alkylene group having 1 to 3 carbon atoms;
[0020] R 5 It represents an alkyl group with 1 to 6 carbon atoms;
[0021] n represents an integer from 1 to 15;
[0022] * indicates the bond with the adjacent structural unit].
[0023] [2] The random copolymer according to [1], wherein the structural unit represented by formula (II) is derived from a monomer having a Tg of -100 to 15°C.
[0024] [3] The random copolymer according to [1] or [2], wherein the amount of the structural unit of formula (I) is 50 to 99 mol % and the amount of the structural unit of formula (II) is 1 to 50 mol % based on the amount of all structural units of the random copolymer.
[0025] [4] The random copolymer according to any one of [1] to [3], which has a weight average molecular weight of 50,000 to 300,000.
[0026] [5] A fine particle adsorbent comprising the random copolymer described in any one of [1] to [4].
[0027] [6] The fine particle adsorbent according to [5], wherein the fine particles are pollen.
[0028] [7] A composition for forming a microparticle-adsorptive coating film, comprising the random copolymer according to any one of [1] to [4].
[0029] [8] The composition for forming a fine particle adsorptive film according to [7], wherein the fine particles are pollen.
[0030] [9] The composition for forming a fine particle-adsorptive coating film according to [7] or [8], further comprising a solvent.
[0031]
[10] A coating formed from the composition for forming a fine particle-adsorptive coating according to any one of [7] to [9].
[0032]
[11] The coating according to
[10] , which has an elastic modulus of 0.1 to 1.0 MPa and an adhesiveness of 1.0 nm / nN or more.
[0033] Effects of the Invention
[0034] According to the present invention, there can be provided a particle adsorbent, particularly a pollen adsorbent, which can adsorb particles of pollen, virus, house dust, etc. while suppressing their breakage. DETAILED DESCRIPTION
[0035] Hereinafter, the embodiments of the present invention will be described in detail. In addition, the scope of the present invention is not limited to the embodiments described here, and various changes can be made within the scope of the present invention.
[0036] The present invention provides a random copolymer containing a structural unit represented by formula (I) and a structural unit represented by formula (II), and a particulate adsorbent containing the random copolymer.
[0037] [Chemistry 2]
[0038]
[0039] [In formula (I) and (II):
[0040] R 1 and R 3 Each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms;
[0041] R 2 It represents an alkyl group with 1 to 6 carbon atoms;
[0042] R 4 It represents an alkylene group having 1 to 3 carbon atoms;
[0043] R 5 It represents an alkyl group with 1 to 6 carbon atoms;
[0044] n represents an integer from 1 to 15;
[0045] * indicates a bond with an adjacent structural unit].
[0046] The copolymer of the present invention is a random copolymer, which randomly has one or more structural units represented by formula (I) and one or more structural units represented by formula (II). The structural unit represented by formula (I) is also called "structural unit (I)", and the structural unit represented by formula (II) is also called "structural unit (II)". The copolymer of the present invention can be a random copolymer composed of structural units (I) and structural units (II), or a random copolymer composed of structural units (I), structural units (II) and other structural units different from these structural units. Surprisingly, according to the copolymer of the present invention having randomly repeated structural units (I) and structural units (II), a coating having high adsorption to particles such as pollen, viruses, and house dust, and also being able to inhibit the rupture of these particles, etc. can be provided. Although the reason is not clear, since the coating formed by the copolymer of the present invention is a coating having adhesion to particles such as pollen, the particles can be attached to the surface. It is known that the attached particles are sometimes damaged by impact during attachment, and in particular, in the case of pollen, they can be broken even by moisture absorption under high humidity conditions. It is believed that on the surface of the film containing the copolymer of the present invention, it is difficult for the particles to be damaged when attached, and depending on the circumstances, the attached particles are at least partially buried in the surface of the film, and as a result, it is believed that the breakage caused by moisture absorption under high humidity conditions is also suppressed. Therefore, the particle adsorbent containing a random copolymer of the present invention is a particle adsorbent that can adsorb particles such as pollen, viruses, and house dust while suppressing their breakage. In addition, the particle adsorbent can be a preparation for imparting adsorption to particles, or it can be a raw material component used in the manufacture of the preparation.
[0047] R in formula (I) 1 represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. Examples of the alkyl group having 1 to 3 carbon atoms include methyl, ethyl, propyl, and 1-methylethyl. From the viewpoint of easy preparation of a random copolymer (easy polymerization with other structural units), R 1 Preferred is a hydrogen atom or a methyl group.
[0048] R in formula (I) 2 R represents an alkyl group having 1 to 6 carbon atoms. Examples of the alkyl group having 1 to 6 carbon atoms include methyl, ethyl, propyl, 1-methylethyl, butyl, isobutyl, tert-butyl, pentyl, and hexyl. From the viewpoint of improving adsorption and suppressing the destruction of fine particles, R 2 The number of carbon atoms is preferably 1 to 5.
[0049] R in formula (II) 3 represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms. Examples of the alkyl group having 1 to 3 carbon atoms include: 1From the perspective of easy preparation of random copolymers (easy polymerization with other structural units), R 3 Preferred is a hydrogen atom or a methyl group.
[0050] R in formula (II) 4 R represents an alkylene group having 1 to 3 carbon atoms. Examples of the alkylene group having 1 to 3 carbon atoms include methylene, ethylene, propylene, and methylethylene. From the viewpoint of suppressing the destruction of the microparticles, R 4 Preferred is a methylene group or an ethylene group.
[0051] R in formula (II) 5 represents an alkyl group having 1 to 6 carbon atoms. Examples of the alkyl group having 1 to 6 carbon atoms include: 2 From the perspective of improving adsorption and inhibiting the destruction of particles, R 5 The number of carbon atoms is preferably 1-5, more preferably 1-4.
[0052] n in formula (II) represents an integer of 1 to 15. From the viewpoint of suppressing the destruction of fine particles, n preferably represents 1 to 12, more preferably represents 1 to 10, and even more preferably represents 1 to 5.
[0053] The random copolymer of the present invention is preferably a polymer having a (meth) acrylic acid skeleton. In addition, in this specification, "(meth) acrylic acid" refers to acrylic acid and / or methacrylic acid. The random copolymer of the present invention is a copolymer containing randomly repeated structural units represented by formula (I) and structural units represented by formula (II), and other structural units as appropriate. The total amount of structural units (I) and structural units (II) relative to the amount of all structural units constituting the random copolymer of the present invention is preferably 50 mol% or more, more preferably 70 mol% or more, further preferably 80 mol% or more, further more preferably 90 mol% or more, and particularly preferably 95 mol% or more. The upper limit of the content ratio is 100 mol% or less.
[0054] The structural unit represented by formula (I) contained in the random copolymer of the present invention is, for example, a structural unit derived from a (meth)acrylic monomer represented by the following formula (Ia):
[0055] [Chemistry 3]
[0056]
[0057] Regarding R in formula (Ia) 1a and R 2a , which are also applicable to R in formula (I) 1 and R 2The (meth)acrylic monomer represented by the formula (Ia) is preferred because it is easy to copolymerize with the monomer represented by the formula (II-a) described later and can easily form a film.
[0058] The structural unit represented by formula (II) contained in the random copolymer of the present invention is, for example, a structural unit derived from a (meth)acrylic monomer represented by the following formula (II-a):
[0059] [Chemistry 4]
[0060]
[0061] Regarding R in formula (II-a) 3a , R 4a and R 5a , which are also applicable to R in formula (II) 3 , R 4 and R 5 Related records.
[0062] In a preferred embodiment of the present invention, from the viewpoint of easily improving the microparticle adsorption of the copolymer of the present invention and the microparticle adsorbent containing the copolymer and the performance of suppressing microparticle breakage, the structural unit represented by formula (II) is preferably derived from a monomer having a Tg (glass transition temperature) of -100 to 15°C. When the copolymer of the present invention has a structural unit represented by formula (II) derived from a monomer having a Tg of -100 to 15°C, a low-Tg flexible structure is randomly incorporated into the copolymer. As a result, it is considered that the adsorption of microparticles can be improved, and the breakage of microparticles can be easily suppressed by the soft structural part. From the viewpoint of easily exerting the effect of the present invention when using the microparticle adsorbent of the present invention, especially when used under a normal temperature environment, and from the viewpoint of operability when the microparticle adsorbent of the present invention is coated on an object, the Tg of the monomer is preferably -90 to 5°C, more preferably -80 to -5°C, and even more preferably -70 to -10°C. The Tg of the monomer can be measured by, for example, the method described in the Examples. In addition, the Tg of the monomer refers to the Tg of the homopolymer of the monomer. As the Tg of a monomer, a known literature value is used when it can be used; when there is no known literature value, for example, the monomer is homopolymerized under the polymerization conditions described in the examples described later to form a homopolymer, and the value obtained by measuring the Tg of the homopolymer is used as the Tg of the monomer.
[0063] Based on the amount of all structural units of the random copolymer of the present invention, the amount of the structural unit of formula (I) is preferably 50 to 99 mol%, and the amount of the structural unit of formula (II) is preferably 1 to 50 mol%. When the amount of the structural unit of formula (II) is above the above lower limit, the adsorption of particles can be improved, and the rupture of particles can be easily suppressed; when the amount of the structural unit of formula (II) is below the above upper limit, it is easy to increase the strength of the coating containing the copolymer of the present invention to a certain extent, and it is easy to maintain the effect of adsorbing particles for a long time. When the amount of the structural unit of formula (I) is above the above lower limit, it is easy to increase the strength of the coating containing the copolymer of the present invention to a certain extent, and it is easy to maintain the effect of adsorbing particles for a long time. In addition, when the amount of the structural unit of formula (I) is below the above upper limit, the adsorption of particles can be improved, and the rupture of particles can be easily suppressed.
[0064] The amount of the structural unit of formula (I) is preferably 50 to 99 mol %, more preferably 60 to 95 mol %, and further preferably 65 to 90 mol %, based on the amount of all structural units of the random copolymer.
[0065] The amount of the structural unit of formula (II) is preferably 1 to 50 mol %, more preferably 5 to 40 mol %, and further preferably 10 to 35 mol %, based on the amount of all structural units of the random copolymer.
[0066] The amount of the structural unit of formula (I) is preferably 50 to 99 mol %, more preferably 60 to 95 mol %, and further preferably 65 to 90 mol %, based on the total amount of the structural unit of formula (I) and the structural unit of formula (II) contained in the random copolymer.
[0067] The amount of the structural unit of formula (II) is preferably 1 to 50 mol %, more preferably 5 to 40 mol %, and further preferably 10 to 35 mol %, based on the total amount of the structural unit of formula (I) and the structural unit of formula (II) contained in the random copolymer.
[0068] As other structural units that may be contained in the random copolymer, there can be mentioned structural units derived from the following monomers:
[0069] Hydroxyl-containing ethylenically unsaturated monomers such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate and hydroxybutyl (meth)acrylate;
[0070] Alkyl (meth)acrylate monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, lauryl (meth)acrylate, and stearyl (meth)acrylate;
[0071] Glycidyl acrylate, glycidyl methacrylate and other glycidyl ethylenically unsaturated monomers;
[0072] Vinyl esters of saturated aliphatic carboxylic acids such as vinyl acetate and vinyl propionate;
[0073] Styrene monomers such as styrene, α-methylstyrene, vinyltoluene, etc.
[0074] (Meth)acrylamide, N-methylol (meth)acrylamide, N-methoxybutyl (meth)acrylamide, diacetone (meth)acrylamide, N, N-dimethylaminopropyl (meth)acrylamide, N-tert-butyl (meth)acrylamide and other amide group-containing ethylenically unsaturated monomers;
[0075] Other ethylenically unsaturated monomers such as N-vinyl pyrrolidone and methoxy polyethylene glycol mono(meth)acrylate.
[0076] These may be used alone or in combination of two or more, as required.
[0077] The weight average molecular weight (Mw) of the random copolymer of the present invention is preferably 5,000 to 1,000,000, more preferably 10,000 to 700,000, further preferably 30,000 to 500,000, and further more preferably 50,000 to 300,000. From the viewpoint of easy application to the object and easy uniform coating, it is preferred that the weight average molecular weight is above the above lower limit; from the viewpoint of improving adsorption and facilitating the suppression of particle destruction, it is preferred that the weight average molecular weight is below the above upper limit. The weight average molecular weight of the random copolymer can be measured by the method described in the examples.
[0078] The number average molecular weight (Mn) of the random copolymer of the present invention is preferably 1,000 to 500,000, more preferably 3,000 to 300,000, further preferably 5,000 to 200,000, and further more preferably 10,000 to 100,000. From the viewpoint of easy application to an object and easy uniform coating, it is preferred when the number average molecular weight is above the above lower limit; from the viewpoint of improving adsorption and facilitating the suppression of particle destruction, it is preferred when the number average molecular weight is below the above upper limit. The number average molecular weight of the random copolymer can be measured by the method described in the examples.
[0079] The polydispersity index (Mw / Mn) of the random copolymer of the present invention is preferably 2.0 to 4.0, and more preferably 2.5 to 3.5. From the viewpoint of easy application to an object and easy uniform coating, it is preferred when the polydispersity index is above the above lower limit; from the viewpoint of improving adsorption and facilitating the suppression of particle destruction, it is preferred when the polydispersity index is below the above upper limit.
[0080] From the viewpoint of improving adsorption and facilitating the suppression of particle destruction, the glass transition temperature Tg of the random copolymer of the present invention is preferably above -60°C, more preferably above -40°C, further preferably above -20°C, and particularly preferably above -10°C; from the same viewpoint, it is preferably below 20°C, more preferably below 15°C, and further preferably below 10°C. The glass transition temperature Tg of the random copolymer of the present invention is obtained by the FOX formula. Specifically, when the Tg of the homopolymer of the first structural unit contained in the copolymer is set to Tg1, the mass fraction of the first structural unit in the copolymer is set to W1, the Tg of the homopolymer of the second structural unit is set to Tg2, and the mass fraction of the second structural unit in the copolymer is set to W2, the Tg0 (K) of the copolymer containing the first structural unit and the second structural unit can be estimated according to the following formula.
[0081] FOX formula: 1 / Tg0=(W1 / Tg1)+(W2 / Tg2)
[0082] From the perspective of improving the strength of the film containing the copolymer and maintaining the particle adsorption effect, the elastic modulus of the random copolymer of the present invention is preferably 0.1 MPa or more, more preferably 0.2 MPa or more, and further preferably 0.3 MPa or more, under the condition of 30-40% RH, when the film formed by applying the random copolymer solution on a sheet made of PET (polyethylene terephthalate) by spin coating and then drying is measured; from the perspective of easily improving the adsorption of particles and easily preventing the adsorbed particles from breaking, it is preferably 1.5 MPa or less, more preferably 1.0 MPa or less, and further preferably 0.8 MPa or less. The elastic modulus can be measured by the method described in the examples.
[0083] From the viewpoint of improving the adsorption of particles and preventing the adsorbed particles from breaking, the adhesion of the random copolymer of the present invention is preferably 0.6 nm / nN or more, more preferably 1.0 nm / nN or more, and further preferably 1.5 nm / nN or more, when the film formed by applying the solution of the random copolymer on a PET sheet by spin coating and drying is measured under the condition of 30-40% RH; from the viewpoint of improving the ease of operation, it is preferably 15 nm / nN or less, more preferably 12 nm / nN or less, and further preferably 10 nm / nN or less. The adhesion can be measured by the method described in the examples.
[0084] From the viewpoint of improving adsorption and inhibiting destruction of microparticles, the surface zeta potential of the random copolymer of the present invention is preferably -4.0 mV or more, more preferably -2.0 mV or more, and further preferably -0.5 mV or more, as measured by the measurement method in the embodiments described later; from the viewpoint of operability, it is preferably 4.0 mV or less, more preferably 2.0 mV or less, and further preferably 1.5 mV or less.
[0085] The random copolymer of the present invention can be prepared by random copolymerization of a monomer mixture containing a monomer providing structural unit (I), a monomer providing structural unit (II), and other monomers as appropriate. The polymerization of the monomer mixture can be carried out by methods commonly used by those skilled in the art, and a method of polymerizing the monomer mixture by heating or light irradiation can be mentioned. As specific polymerization methods, bulk polymerization, precipitation polymerization, suspension polymerization, emulsion polymerization, solution polymerization, and overall polymerization can be mentioned. Among the above-mentioned polymerization methods, when considering use as a particulate adsorbent, it is more preferably prepared by a solution polymerization method in which it is pre-copolymerized in water, a hydrophilic solvent, or a mixture thereof.
[0086] In this specification, a hydrophilic solvent refers to an organic solvent having a solubility in water of 10 g / 100 g of water (25° C.) or more. Specific examples of such hydrophilic solvents include aliphatic mono- to tetra-hydric alcohols having 1 to 4 carbon atoms, ethyl cellosolve, butyl cellosolve, dioxane, methyl acetate, dimethylformamide, and the like. Among the above hydrophilic solvents, mono- to di-hydric alcohols are particularly preferably used.
[0087] Examples of the monohydric alcohol include methanol, ethanol, isopropanol, etc. Examples of the dihydric alcohol include propylene glycol, etc. Among them, ethanol and isopropanol are particularly preferred.
[0088] The solution polymerization of the monomer mixture can be carried out by dissolving the monomer mixture in a solvent such as water, a mixture of water and a hydrophilic solvent, or a hydrophilic solvent, adding a polymerization initiator, and then stirring while heating. The polymerization is more preferably carried out under an inert gas atmosphere such as nitrogen or argon.
[0089] As the polymerization initiator, substances generally used in solution polymerization can be used. Examples of the polymerization initiator include peroxides such as benzoyl peroxide and lauroyl peroxide; azo compounds such as azobisisobutyronitrile, etc. From the viewpoint of controlling the polymerization reaction, it is more preferable to use azo compounds among the above-mentioned polymerization initiators.
[0090] In the above-mentioned polymerization, it is preferred to adjust the amount of the above-mentioned solvent in such a way that the concentration of the mixture of the monomer components reaches about 30 to 60% by weight. The polymerization temperature and polymerization time can be appropriately selected according to the type of monomers contained in the monomer mixture, the type of polymerization initiator, the size of the reaction scale, etc. For example, it is preferred to polymerize at a temperature close to the reflux temperature of the polymerization solvent. The polymerization time is preferably more than 8 hours, more preferably 12 to 36 hours.
[0091] [particle]
[0092] The random copolymer of the present invention can be used as a particle adsorbent containing the random copolymer. The particle adsorbent is a reagent having a particle adsorption effect. Specifically, it can be, for example, a particle adsorption product that can temporarily impart particle adsorption to a coating / spraying object, or a raw material for manufacturing the particle adsorption product. Examples of particles include pollen, viruses, bacteria, fungi, dust (e.g., from soot, dust, sulfur oxides (SO x ), nitrogen oxides (NO x), particulate matter (PM2.5) such as gaseous air pollutants such as volatile organic compounds (VOC), yeast, protozoa, spores, animal skin fragments, mite feces, mite corpses, and house dust that may contain them. From the viewpoint of easy acquisition of particle adsorption, the particles are selected from the group consisting of viruses, bacteria, fungi, dust, yeast, protozoa, spores, animal skin fragments, mite feces, mite corpses, and house dust that may contain them, among which pollen is preferred. The particles are, for example, particles of a size that can float in the atmosphere (preferably a diameter of 60 μm or less, more preferably 30 μm or less, and further preferably 20 μm or less), preferably pollen and / or virus, more preferably pollen.
[0093] Examples of pollen include pollen from plants of the Cypress family (e.g., the genera Fir and Chamaecyparis), pollen from plants of the Poaceae family (e.g., the genera Dactylum and the genera Timothy), pollen from plants of the Asteraceae family (e.g., the genera Ambrosia and the genera Artemisia), and pollen from plants of the Betulaceae family (e.g., the genera Betula platyphylla). However, the types of pollen are not limited to the above.
[0094] Examples of the virus include influenza virus, herpes virus, rubella virus, coronavirus, Ebola virus, hepatitis virus, rabies virus, norovirus, rotavirus, polio virus, and adenovirus, but the types of the virus are not limited to those listed above.
[0095] Examples of bacteria include Gram-positive bacteria (eg, Staphylococcus, Streptococcus, Bacillus subtilis, Mycobacterium tuberculosis, Clostridium botulinum, etc.) and Gram-negative bacteria (eg, Escherichia coli, Salmonella, Pseudomonas aeruginosa, Vibrio cholerae, etc.), but the types of bacteria are not limited to those listed above.
[0096] Examples of fungi include Trichophyton, Candida, and Aspergillus, but the types of fungi are not limited to those listed above.
[0097] Examples of dust include particulate matter (PM2.5), soot (sulfur oxides (SO x ), smoke (so-called coal dust), harmful substances (cadmium and its compounds, chlorine and hydrogen chloride, fluorine, hydrogen fluoride and silicon fluoride, lead and its compounds, and nitrogen oxides (NO x ) etc., but the types of dust are not limited to those described above.
[0098] Examples of the microparticles include yeast, protozoa, spores, animal skin fragments, mite feces, and mite corpses.
[0099] Examples of house dust include those containing at least two or more of the above-mentioned pollen, virus, bacteria, fungi, dust and fine particles.
[0100] [Microparticle adsorbent]
[0101] In addition to the random copolymer of the present invention described above, the particulate adsorbent may also contain a medium such as a solvent. The solvent is not particularly limited, and examples thereof include water, hydrophilic solvents, or mixtures thereof as described above. The dosage form of the particulate adsorbent is not particularly limited, and examples thereof include liquid, gel, spray, mist, emulsion (lotion), cream, lotion, foundation, outer coating agent, detergent, etc. The type of medium can be appropriately selected according to the dosage form of the particulate adsorbent. In addition, the particulate adsorbent may also contain additives such as surfactants, ultraviolet absorbers, antioxidants, and fragrances. That is, when the particulate adsorbent of the present invention contains ultraviolet absorbers, antioxidants, etc. in the particles of the adsorption object, these particles can be inhibited from falling off from the surface of the coated object, so that it can be expected that the effect brought by these particles can be maintained.
[0102] By applying or spraying the particle adsorbent of the present invention on, for example, filters, bodies, hair, clothing, bedspreads, accessories (e.g., masks, glasses, goggles, hats, scarves, silk scarves, etc.), the copolymer of the present invention can be imparted to these objects, thereby imparting particle adsorbability.
[0103] The particle adsorbent of the present invention may be, for example, a composition for forming a particle-adsorbing film containing the random copolymer of the present invention. The present invention also provides the composition for forming a particle-adsorbing film. The composition for forming a particle-adsorbing film is a composition for forming a film having particle adsorption, and its dosage form is not particularly limited. For example, it may be a liquid composition containing the copolymer of the present invention and at least one solvent. The composition for forming a particle-adsorbing film is applied to an object by coating, spraying, etc., and then the composition is dried, so that a particle-adsorbing film can be formed on the object. As solvents and other components that may be contained in the composition for forming a particle-adsorbing film, the solvents and components described above in connection with the particle adsorbent can be cited.
[0104] The content of the copolymer of the present invention contained in the particulate adsorbent of the present invention can be appropriately adjusted according to the purpose of the particulate adsorbent, but from the viewpoint of the effect of easily improving the adsorption of particulates, based on the solid content of the particulate adsorbent, as an example, it is 1% by mass or more, 3% by mass or more, 5% by mass or more, or 10% by mass or more.
[0105] The present invention also provides a film formed by the above-mentioned composition for forming a microparticle-adsorbing film. That is, the film of the present invention is a film containing a random copolymer having a structural unit represented by the above-mentioned formula (I) and a structural unit represented by the formula (II). The method for forming the film is not particularly limited, and the composition for forming a microparticle-adsorbing film of the present invention can be applied to an object by coating, spraying, etc., and then the composition can be dried to distill off the solvent, etc.
[0106] From the viewpoint of improving the strength of the coating containing the copolymer and maintaining the particle adsorption effect, the elastic modulus of the coating of the present invention is preferably 0.1 MPa or more, more preferably 0.2 MPa or more, and further preferably 0.3 MPa or more; from the viewpoint of easily improving the adsorption of particles and easily preventing the adsorbed particles from rupturing, the elastic modulus of the coating of the present invention is preferably 2.5 MPa or less, more preferably 1.5 MPa or less, further preferably 1.0 MPa or less, and particularly preferably 0.7 MPa or less. The elastic modulus can be measured using the method described in the examples, for example. The above elastic modulus is measured under the condition of humidity 30~35% RH as described in the examples.
[0107] From the perspective of easily improving the adsorption of particles and easily preventing the adsorbed particles from breaking, the adhesion of the coating of the present invention is preferably 0.6 nm / nN or more, more preferably 1.0 nm / nN or more, and further preferably 2.0 nm / nN or more; from the perspective of operability, it is preferably 6.0 nm / nN or less, more preferably 5.0 nm / nN or less, further preferably 4.0 nm / nN or less, and further more preferably 3.5 nm / nN or less. The adhesion can be measured using the method described in the examples. The above-mentioned adhesion is measured under the condition of humidity 30~35%RH as described in the examples.
[0108] From the viewpoint of easily improving the adsorption of particles, the surface zeta potential of the coating of the present invention is preferably -10 mV or more, more preferably -5.0 mV or more, further preferably -3.0 mV or more, and particularly preferably -1.5 mV; from the viewpoint of easily improving the adsorption of particles, it is preferably 10 mV or less, more preferably 5.0 mV or less, and further preferably 3.0 mV or less. The surface zeta potential can be measured by the method described in the examples.
[0109] Example
[0110] Next, the present invention will be described in more detail using examples, but the present invention is not limited to the following examples. In addition, "%" and "part" in the examples represent "mass %" and "mass part", respectively, unless otherwise specified.
[0111] (Glass transition temperature Tg of monomer)
[0112] The Tg of a monomer refers to the Tg of the homopolymer of the monomer. If there is a known literature value for the Tg of a monomer, that value is used; if there is no known literature value, the monomer is homopolymerized under the following polymerization conditions to form a homopolymer, and the value obtained by measuring the Tg of the homopolymer is used as the Tg of the monomer.
[0113] Aggregation conditions
[0114] The monomer and polymerization initiator were injected into the molding mold (release films were respectively pasted on two glass plates, and the surfaces of the release films were placed opposite to each other. A 4 mm thick silicon spacer was placed between them to form a region of 100 mm in length and 100 mm in width, and the silicon spacer was sandwiched between two glass plates at an interval of about 2 to 4 mm). The molding mold was irradiated with ultraviolet rays (wavelength: 365 nm) for 1 hour using an LED exposure machine to obtain a polymer. 10 mg of the obtained polymer was weighed and installed in a differential scanning calorimeter (DSC7000X, manufactured by Hitachi High-Technologies Co., Ltd.), and measured at a heating rate of 10°C / min and a temperature range of -130 to 100°C. The temperature of the endothermic peak from the polymer during the first heating process was taken as the glass transition temperature (Tg) of the polymer, and it was also taken as the Tg of the monomer.
[0115] (Glass transition temperature Tg of random copolymer)
[0116] The glass transition temperature Tg of the random copolymer of the present invention is determined by the FOX equation as described above. In addition, when all the monomers used react to form a random copolymer, the FOX equation is also applicable. The same is true for each copolymer and homopolymer in the comparative examples described below.
[0117] (Weight average molecular weight Mw, number average molecular weight Mn, Mw / Mn)
[0118] The weight average molecular weight (Mw) and the number average molecular weight (Mn) are measured in accordance with JIS K7252-1: 2016. In addition, all values are based on polystyrene standard samples.
[0119] Table 1 shows the structures, Tg, and molecular weights of monomers used in the examples and comparative examples described below.
[0120] [Table 1]
[0121]
[0122] The monomers used in the present examples and comparative examples, except for PEGMEMA, were commercially available products sold by Wako Pure Chemical Industries, Ltd. PEGMEMA was M-90G manufactured by Shin-Nakamura Chemical Co., Ltd.
[0123] [Example 1]
[0124] In a 500 ml five-necked flask equipped with a reflux cooler, a thermometer, a nitrogen inlet pipe, a feed pipe and a stirring device, a monomer mixture formed by 30 parts (mass parts, the same below) of methoxyethyl acrylate and 70 parts of butyl methacrylate and 150 parts of anhydrous ethanol were added, and 0.2 parts of α, α'-azobisisobutyronitrile (hereinafter referred to as AIBN) were added thereto, and heated to reflux at 80°C under a nitrogen flow while stirring. The obtained resin composition was diluted with ethanol to a concentration of 10% by mass to obtain a 10% ethanol solution of a BMA / MEA random copolymer. The weight average molecular weight and number average molecular weight of the obtained BMA / MEA random copolymer were measured, and the results are shown in Table 2.
[0125] [Example 2 and Comparative Examples 1 to 5]
[0126] Each polymer and a 10 mass % ethanol solution were prepared in the same manner as in Example 1, except that the type and amount of each monomer contained in the monomer mixture were changed as shown in Table 2 below, and each property was measured.
[0127] [Evaluation of coating]
[0128] (Surface Zeta Potential)
[0129] 0.4 mL of the 10% by mass ethanol solution in each embodiment and comparative example was dropped onto a PET sheet (manufactured by AS ONE, thickness: 1 mm, 15×30 mm), and spin-coated with a commercially available spin coater to form a coating. Spin coating was performed at 500 rpm for 10 seconds, and then at 2000 rpm for 60 seconds to produce a PET sheet test piece in each embodiment and comparative example. The test piece was placed in a quartz sample cell for flat-plate ZETA potential measurement (manufactured by Otsuka Electronics) and measured with a commercially available ZETA potential measurement system (ELSZ-2000Z manufactured by Otsuka Electronics). Specifically, a solution of monitoring particles (manufactured by Otsuka Electronics) dispersed in a 10 mM sodium chloride aqueous solution was flowed into the measurement sample cell of the ZETA potential measurement system to measure the surface ZETA potential.
[0130] (Elastic modulus of coating)
[0131] 0.4 mL of the 10 wt% ethanol solution in each example and comparative example was dripped onto a PET sheet (manufactured by AS ONE, thickness: 1 mm, 10×10 mm), and a commercially available spin coater was used to perform spin coating to form a coating. Spin coating was performed at 500 rpm for 10 seconds, and then at 2000 rpm for 60 seconds to produce a PET sheet test piece in each example and comparative example. Each test piece was placed on a scanning probe microscope (SPM-9700 manufactured by Shimadzu Corporation), and the force curve data was measured using a cantilever. The force curve obtained was analyzed based on the JKR contact theory using the accompanying analysis software (Hertz contact solution (when the surface is non-adhesive), or the two-point JKR method (an improved fitting formula of the Hertz contact solution after considering adhesion energy)), and the elastic modulus distribution was obtained. The obtained data was analyzed using the accompanying analysis software to obtain the elastic modulus.
[0132] The cantilever used for measurement and the measurement conditions are shown below.
[0133] <Cantilever>
[0134] ˙Test piece with humidity of 30~35%RH: SD-R30-FM (manufactured by NANOSENSORS, Spring constant (kc) = 2.8N / m, Resonant frequency (resonant frequency) = 75kHz, Curvature radius (curvature radius, R) = 2μm
[0135] ˙Test piece with humidity of 90~95%RH: Particle probe (made by Novascan, Spring constant (kc) = 0.12N / m, Resonant frequency = 70kHz, Particle size (Curvature radius) (R) = 10μm)
[0136] <Measurement conditions>
[0137] ˙Operation point of cantilever surface: 0.5V
[0138] ˙Force curve measurement: 0V
[0139] ˙Cantilever swing speed: 0.5Hz
[0140] (Adhesion of film)
[0141] Adhesion was evaluated based on the distance (nm) of movement of the cantilever required to peel off the cantilever from the coating until the force is no longer applied relative to the force (Force, nN) applied when the cantilever contacts the coating, which was read from the force curve data obtained in the measurement of the elastic modulus of the coating. That is, the distance (nm) required to peel off the cantilever adhered to the coating was divided by the force (nN) applied when the cantilever contacts the coating (nm / nN, distance per unit force) and was regarded as the adhesion of the coating.
[0142] Adhesion is defined by the force (Force, nN) applied when the cantilever contacts the polymer film relative to the force curve data obtained from the measurement of the above (elastic modulus of the coating), and the cantilever movement distance (nm) required to peel the cantilever from the polymer film until the force is no longer applied. That is, the evaluation is performed based on the distance (nm / nN, distance per unit force) required to peel the cantilever adhered to the polymer film.
[0143] <Preparation of Nonwoven Fabric Test Specimen>
[0144] A commercially available nonwoven fabric (medical gauze, manufactured by Terumo) was immersed in the 10 mass % ethanol solution obtained in the examples and comparative examples and allowed to stand for 5 minutes. Next, the nonwoven fabric was fished out of the solution, and after removing the excess solution, it was dried at room temperature and pressure to produce a nonwoven fabric test piece with the copolymer of each example and comparative example attached to the surface. The obtained nonwoven fabric test piece was used to conduct the same test as the pollen adsorption evaluation described later, and the obtained test piece was observed under a microscope. As a result, it was confirmed that in the case of the polymers of Examples 1 and 2, the unbroken pollen was adsorbed at a high density. On the other hand, in the case of the polymers of the comparative examples, the adsorption density of the pollen was low, and pollen rupture was also confirmed in some comparative examples.
[0145] The physical properties of the copolymers obtained in Examples and Comparative Examples and the films obtained using the film-forming compositions containing the copolymers were measured.
[0146] [Table 2]
[0147]
[0148] [Evaluation of pollen adsorption]
[0149] (Preparation of test pieces)
[0150] A 5 mass % ethanol solution of each polymer of the Examples and Comparative Examples was prepared, and a PET sheet of a specific size (manufactured by AS ONE, thickness 1 mm, for measuring pollen density: 20 mm × 20 mm, for measuring the number of damaged pollen: 15 mm × 15 mm) was immersed in the solution for one day, then washed with ethanol and dried with nitrogen gas to prepare a test piece in which each polymer was laminated on a glass substrate. Each test piece was fixed on a glass substrate with a bottom area of 100 cm 2 In a sealed plastic container that has been anti-statically processed.
[0151] (Measurement of pollen density and destruction rate under low humidity)
[0152] The test piece prepared as described above was left to stand at room temperature and 30-40% RH for 2 hours. After that, 10 mg of each pollen particle was placed in a sealed container, maintained at 30-40% RH at room temperature, and placed on a commercially available vibrator while vibrating for 10 hours. Next, the test piece was taken out, and nitrogen was blown to remove the pollen accumulated on the surface, and a pollen adsorption test piece was prepared. In addition, each pollen particle used a commercially available pollen particle.
[0153] The pollen adsorption test piece obtained by the method of observing the unit area of 0.55 mm2 was adsorbed on the pollen adsorption test piece by an optical microscope (magnification 10 times). 2 The number of pollens within the range was calculated to determine the number of pollens adsorbed by each test piece (pollen density). In addition, the number of pollens destroyed per unit area was measured using SEM images, and the destruction rate of each polymer was calculated using the following formula.
[0154] Destruction rate (%) = (number of pollens destroyed / number of pollens adsorbed) × 100
[0155] In addition, whether the pollen is damaged is determined by whether cracks occur on the pollen surface.
[0156] (Measurement of pollen density and destruction rate under high humidity)
[0157] The pollen density and destruction rate under high humidity were measured in the same manner as the measurement of the pollen density and destruction rate under low humidity, except that the conditions for the stationary and vibrating test pieces were changed to room temperature and 90 to 95% RH.
[0158] (Dependence of the destruction rate on humidity)
[0159] The dependence of the destruction rate on humidity (destruction rate B / A) is obtained by the following formula: It is known that the smaller the value, the more the pollen rupture is suppressed even under high humidity conditions where pollen is easily ruptured.
[0160] Dependence of the damage rate on humidity = (damage rate at humidity 90~95%RH) / (damage rate at temperature 30~40%RH)
[0161] The films obtained using the film-forming compositions containing the polymers obtained in the Examples and Comparative Examples were evaluated for pollen adsorption according to the above method, and the results are summarized in Table 3. It can be seen that the films obtained using the film-forming compositions containing the random copolymers of the Examples were excellent in pollen adsorption and could suppress pollen destruction.
[0162] [Table 3]
[0163]
Claims
1. A random copolymer having a structural unit represented by formula (I) and a structural unit represented by formula (II): [Chemistry 1] In formula (I) and (II): R 1 and R 3 Each independently represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms; R 2 It represents an alkyl group with 1 to 6 carbon atoms; R 4 It represents an alkylene group having 1 to 3 carbon atoms; R 5 It represents an alkyl group with 1 to 6 carbon atoms; n represents an integer from 1 to 15; * indicates the bond with the adjacent structural unit.
2. The random copolymer according to claim 1, wherein The structural unit represented by formula (II) is derived from a monomer having a Tg of -100 to 15°C.
3. The random copolymer according to claim 1, wherein The amount of the structural unit of formula (I) is 50 to 99 mol %, and the amount of the structural unit of formula (II) is 1 to 50 mol %, based on the amount of all structural units of the random copolymer.
4. The random copolymer according to claim 1, having a weight average molecular weight of 5,000 to 1,000,000. 5 . A fine particle adsorbent comprising the random copolymer according to claim 1 .
6. The particulate adsorbent according to claim 5, wherein: The particles are pollen. 7 . A composition for forming a fine particle-adsorptive coating film, comprising the random copolymer according to claim 1 .
8. The composition for forming a microparticle-adsorptive film according to claim 7, wherein The particles are pollen. 9 . The fine particle-adsorptive film-forming composition according to claim 7 , further comprising a solvent. 10 . A coating formed from the fine particle-adsorbing coating-film-forming composition according to claim 7 . 11 . The coating according to claim 10 , having an elastic modulus of 0.1 to 1.0 MPa and an adhesiveness of 1.0 nm / nN or more.
Citation Information
Patent Citations
Allergen absorbent composition
JP2002167332A
Pollen adsorbent material and mask
WO2008153090A1